ROUTINE BIOCHEMICAL DIAGNOSIS AND PROGNOSIS OF COVID-19 SEVERITY IN THE CONDITIONS OF THE REGIONAL HOSPITAL - Komarevtseva, I.O.; Balabanova, K.V.; Ovcharenko, M.O.; Usatov, S.A.; Komarevtsev, V.M.; Frolova, I.V.; Zielonyi, I.I. (World of Medicine and Biology, 2024)
The purpose of the study was to evaluate routine laboratory indicators of biochemical blood analysis as markers of potential risk and factors of infection with COVID-19 and the severity of respiratory failure in both women and men. This single-center retrospective study was conducted with the participation of 57 COVID-19-positive individuals hospitalized at the Rivne Regional War Veterans Hospital in October-November 2021. Blood urea levels were higher in respiratory failure group 1 than in respiratory failure group 2 in both women and men. The dynamics of creatinine levels in women and men with COVID-19 in all groups were the same. as well as blood urea levels. The level of total protein in women with COVID-19 decreased with the progression of respiratory failure to stage II, while in men, on the contrary, it increased. Female COVID-19 patients with grade I respiratory failure have higher total protein than male grade I respiratory failure, and female patients with grade 2 respiratory failure have lower total protein levels in women than in men. The dynamics of the level of albumin in women and men with COVID-19 in all groups was the same as the level of total protein. Based on ROC analysis, Kaplan-Meier method; univariate analysis using the log-rank test and the Cox regression model found that blood urea and creatinine levels are biomarkers of the development of respiratory failure (I or II) within 30 days after hospitalization in patients with COVID-19, both women and men.